Commentary: (How) does the experience of parental divorce in childhood contextualize adult development? Reflections on Fergusson et al. (2014). (14th March 2014) - Tasker, Fiona
<x xml:space="preserve">Abstract</x> Fergusson, McLeod, and John Horwood (2014) have raised many interesting issues in their article considering the effects of parental separation/divorce in childhood on later adult partnership outcomes. In particular the article has contributed to our knowledge of the intergenerational transmission of marital instability. In my Commentary article I have: (a) situated the Christchurch Health and Development Study (CHDS) findings within the substantial body of literature on the intergenerational transmission of marital instability, (b) placed these findings within their sociocultural context, and (c) considered their clinical implications. I then consider the important role that the CHDS study has played in revealing the relative contributions of childhood family structure, social context, and family processes to patterns of intimate relationship formation in adulthood.